Depression mediates cutaneous body image and facial appearance dissatisfaction in insomnia - Akram, U; Irvine, K (Springer, 2020)
This study examined the relationship between dissatisfaction with cutaneous body image and facial appearance with symptoms of insomnia whilst incorporating the mediating role of anxiety and/or depression after accounting for co-morbid sleep disorder symptoms. Participants (n = 241) completed online measures assessing insomnia symptoms, anxiety and depression symptoms, and satisfaction with cutaneous body image and facial appearance. Symptoms of insomnia were independently related to greater dissatisfaction with cutaneous body image and facial appearance in univariate analyses. However, linear regression analyses determined these relationships to be partially mediated by depression, but not anxiety. Expanding on prior research, these findings suggest that whilst increased symptoms of insomnia may influence dissatisfaction with cutaneous and facial features, these relationships may be partially attributed to the experience of depressive symptoms often co-morbid with both insomnia and dermatological complaints. Treatment approaches for individuals with insomnia may benefit from targeting and improving negatively appraised aspects of physical self-perception.